Minimum Service Standards (MSS) towards Society 5.0 (Universitas Terbuka, 2023)
Society 5.0 is a community that exists between two worlds, namely the virtual world and the physical real world, which are interconnected. One of its characteristics is the utilization of artificial intelligence (AI) that aids in the work processes. The goal of Society 5.0 is to provide a positive impact on economic and social issues. This research aims to analyze the government's minimal service standards (SPM) or bureaucracy towards Society 5.0 services. The research methodology employed in this study is qualitative, with the collection of secondary data sourced from government RPJMD reports, regional government (OPD) work plans and strategic plans, journals, and books related to the research focus. Data analysis is conducted using the interactive data analysis model by Miles and Huberman. The findings of this research indicate that the Minimal Service Standards (SPM) of Bondowoso Regency encompass 6 (six) services, namely the services in the fields of Education, Health, Public Works and Spatial Planning, People's Housing and Settlements, Security, Public Order and Community Protection, as well as Social Affairs. The implementation is still not carried out to its maximum potential, thus the journey towards Society 5.0 has not been fully realized and remains a task for the local government concerning the utilization of technology and information in the orientation of public services towards community well-being.